Particle shock acceleration in astrophysics - Meli, Athina; Mastichiadis, Apostolos (2008)
The Fermi (diffusive) particle acceleration in astrophysical shocks is reviewed and evaluated. We discuss their properties and we present Monte Carlo simulations studying the shocks’ efficiency in accelerating particles (i.e. protons) up to very high energies with an application to astrophysical regions such as Supernovae, Active Galactic Nuclei hot spots and Gamma Ray Bursts. We find that the efficiency of the acceleration mechanism at shocks, varies in regard to the inclination of the magnetic field and the shock normal (e.g. sub-luminal shocks, super-luminal shocks), with consequences to the contribution of the very high energy particles to the observed cosmic ray spectrum.